ANALISIS PREFERENSI SISWA SMA DI KOTA SEMARANG TERHADAP PROGRAM STUDI DI PERGURUAN TINGGI DENGAN METODE CHOICE-BASED CONJOINT - Anggreani, Dini; Mukid, Moch. Abdul; Rusgiyono, Agus (Jurnal Gaussian, 2013)
This research aims to determine the design of study program that has the biggest opportunity to be chosen by the students. One method can be used to determine the preferences of high school students on existing study program in college is choice-based conjoint method. Variables used in this research are a minimum value of accreditation of selected study program that consist of three categories (A, B, and C), field of science study program that consist of two categories (exact sciences and not exact sciences), type of study program that consist of two categories (educational and not educational), and education level that consist of three categories (S1, D4, and D3). Data analysis techniques used in the choice-based conjoint method is conditional logit model. Variables order starting from the biggest contribution in influencing students preferences is accreditation of study program, level of education, type of study program, and field of science. The design of study program most likely to be chosen by the students is a study program with accreditation A, not exact sciences field, not educational type, and S1 level.